Capitalized money, austerity and the math of capitalism. (March 2020) - DiMuzio, Tim; Robbins, Richard
This article seeks to contribute to the existing critical debates on money and debt by advancing three main arguments. First, largely due to such debates' tendency for description, the article argues that in in the heterodox literature on money and debt there is no convincing critical theory of money creation. For this reason the authors introduce the theory of capital as power and how it can help us theorize the consequences of present money creation. Second, the authors demonstrate how the capitalization of money creation by a minority of investors not only leads to the political chase for unsustainable economic growth, but also how there is a differential distribution of interest upwards that helps generate greater economic inequality in the United States. Third, they argue that in an era of declining growth, dominant owners of capital seek to recapture their expected return on investments by extracting a greater share of the national income from the vast majority of citizens through a fiscal politics of austerity.